Meaningful Tourism in Africa - Amir Mamah Adamu; Eyong Ayuk Ako-Ebot; Richard Julius; Frederick Kasese; Brigit Murugi; Aisha Hussein Mussa; Angela Njehia; Biubwa Omar; Ropafadzaishe Rushwaya; Wolfgang Georg Arlt (Bali Journal of Hospitality, Tourism and Culture Research, 2025)
This article examines the application of the Meaningful Tourism paradigm in Africa, a continent experiencing the world's fastest tourism growth yet capturing only 5% of global arrivals. Through a qualitative, multi-case study analysis of Cameroon, Kenya, South Africa, Tanzania, Zimbabwe, and Zanzibar, it investigates how this framework addresses critical challenges including economic leakage, environmental pressure, and uneven community benefits. The findings demonstrate that Meaningful Tourism provides a practical toolkit for fostering inclusive growth, enhancing destination resilience, and ensuring measurable value for all six core stakeholders: visitors, host communities, employees, businesses, government, and the environment. The study concludes that adopting this stakeholder-centric approach is essential for transforming Africa's tourism from quantitative expansion into a force for sustainable development and long-term competitiveness. The research offers practical pathways for policymakers and contributes to academic discourse on sustainable tourism in emerging economies.